Parallel transmission 2D RARE imaging at 7T with transmit field inhomogeneity mitigation and local SAR control - Yetisir, Filiz; Poser, Benedikt A.; Grant, P. Ellen; Adalsteinsson, Elfar; Wald, Lawrence L.; Guerin, Bastien (Magnetic resonance imaging, 2022)
We develop and test a parallel transmit (pTx) pulse design framework to mitigate transmit field inhomogeneity with control of local specific absorption rate (SAR) in 2D rapid acquisition with relaxation enhancement (RARE) imaging at 7T. We design large flip angle RF pulses with explicit local SAR constraints by numerical simulation of the Bloch equations. Parallel computation and analytical expressions for the Jacobian and the Hessian matrices are employed to reduce pulse design time. The refocusing-excitation “spokes” pulse pairs are designed to satisfy the Carr-Purcell-Meiboom-Gill (CPMG) condition using a combined magnitude least squares-least squares approach. In a simulated dataset, the proposed approach reduced peak local SAR by up to 56% for the same level of refocusing uniformity error and reduced refocusing uniformity error by up to 59% (from 32% to 7%) for the same level of peak local SAR compared to the circularly polarized birdcage mode of the pTx array. Using explicit local SAR constraints also reduced peak local SAR by up to 46% compared to an RF peak power constrained design. The excitation and refocusing uniformity error were reduced from 20%–33% to 4%–6% in single slice phantom experiments. Phantom experiments demonstrated good agreement between the simulated excitation and refocusing uniformity profiles and experimental image shading. PTx-designed excitation and refocusing CPMG pulse pairs can mitigate transmit field inhomogeneity in the 2D RARE sequence. Moreover, local SAR can be decreased significantly using pTx, potentially leading to better slice coverage, enabling larger flip angles or faster imaging. •An arbitrary FA pTx pulse design algorithm with local SAR constraints was developed.•Refocusing nonuniformity was reduced by up to 59% compared to CP mode.•Peak local SAR was reduced by up to 56% compared to CP mode.•Excitation-refocusing pulses for RARE imaging were validated in phantom experiments.